Guía de procedimientos para la administración de inventarios en el almacén de repuestos de la cooperativa de transportes Loja - Celi Feijoo, Evelin Maribel (2019)
The present thesis work called "GUIDE OF PROCEDURES FOR THE ADMINISTRATION OF INVENTORIES IN THE WAREHOUSE OF SPARE PARTS OF THE COOPERATIVE OF TRANSPORTES LOJA" was carried out in order to know and improve the activities carried out in the company, contributing in the administration and control of the spare parts of the warehouse, this situation allows in turn the timely knowledge of the stock of spare parts maintained by the company, achieving customer satisfaction at an opportune and appropriate time. In compliance with the objectives set out, the procedures were developed that guarantee the adequate control and administration of the inventories; likewise it was possible to develop the necessary flowcharts the same as the actions or activities undertaken by the custodians of the warehouse, allowing them to keep an orderly record of the inventories, strengthening the knowledge of the activities that each of the warehouse employees must develop , when carrying out the present research work it was concluded that the implementation of a procedure guide for the administration of the inventories in the spare parts warehouse of the Cooperativa de Transportes Loja, will allow the company to know the importance of being able to administer the way correct spare parts. Among the main results in the practical execution consists of: the interview with the manager, the accountant and the warehouse personnel in which it was known how the inventory management has been given inside the spare parts warehouse of the Cooperativa de Transportes Loja, likewise, the procedures, policies and flowcharts were carried out that will be the guide to develop the activities in an adequate and timely manner. The conclusions reached once the research work is completed are summarized in the implementation of a procedure guide for the administration of inventories in the spare parts warehouse of the Loja Transport Cooperative, which will allow the company to know the importance of being able to administer the spare parts in the correct way and improve financial returns over time.